Chemical sensing using carbon quantum dots for the detection of cobalt and cyanide ions - Oliveira, José Joelson Pires (2024)
Carbon Quantum Dots (CQDs) are fluorescent, biocompatible nanoparticles, with low toxicity and a structure full of hydrophilic surface groups that guarantee their good dispersibility in water. All these properties make this nanomaterial an excellent candidate for applications in chemical sensing, using its fluorescence as a response signal. In this thesis, several sensing strategies are described such as turn-off sensing, where the fluorescence of CQDs is quenched by the addition of the Co2+ analyte; colorimetric sensor, based on the absorbance of CQDs/Co2+ at 315 nm; turn-off/turn-on sensing, where Fe3+ ions quench the fluorescence of CQDs, but the signal is recovered by the addition of the CN− analyte; and sensor array, which uses multivariate analysis algorithms (chemometric tools), such as principal component analysis (PCA) and linear discriminant analysis (LDA), in order to discriminate analytical signals as in a fingerprint. The results presented in this work report the capacity and versatility of CQDs by functioning as sensitive fluorescent nanoprobes, capable of detecting Co2+ ions in a real sample of blood plasma with recovery of 100.94%, CN− ions in a real sample of tap water with recovery of 94.8% and discriminating with 100% of accuracy (based on LDA) different species present in biscuit formulations, including gluten. Thus, this research promotes CQDs as alternative chemical sensors, contributing to the establishment of a standard method for detecting Co2+ ions and in the field of food safety, quantifying CN−and detecting gluten.